Analisis E-Servqual Terhadap Customer Satisfaction dan Customer Loyalty pada Aplikasi BSI Mobile - Azizah A, Nur; Hidayat, Muhammad Rahmat (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2022)
This study aims to analyze E-service quality on customer satisfaction and customer loyalty to customers who use the BSI mobile application at BSI Meulaboh Imam Bonjol Branch Office. The population in this study are all BSI customers who use the BSI mobile application with a total sample of 105 respondents. This study uses a descriptive research type with a quantitative approach and partial least squares analysis assisted by Smart PLS 3 software. The equation models analyzed are the outer model, inner model and hypothesis testing by analyzing the results of path coefficients which are evaluated through bootstrapping calculations. Based on these results, it was found that the e-service quality of all indicators was only tangibles indicators which had a significant impact on customer loyalty but did not have a significant impact on customer satisfaction using the BSI mobile application. Meanwhile, the variable customer satisfaction on customer loyalty has a significant impact, which means that when customers are satisfied, they will be loyal in using the BSI mobile application.